Assesment of Fiscal Decentralization of the RA Local Self-Government System - Movsisyan, Manuk; Karapetyan, Tsovinar; Ohanyan, Taguhi; Minasyan, Anna («Տնտեսագետ» հրատ․)
Despite being widely used and well examined, fiscal decentralization is often perceived differently. Like other types of decentralization, fiscal decentralization means the transfer of powers and responsibilities from the central government level to local selfgovernment bodies with a certain degree of autonomy. The effectiveness of fiscal decentralization is primarily determined by the approaches used to allocate revenues to the budgets of different levels of government, as well as by the organization of interbudgetary relations. It is obvious that compliance of fixed revenues (first of all tax revenues) with the expenditure part of the budget is of great importance for the implementation of spending powers assigned to local self-government bodies. In the given paper, by calculating the indicators used in domestic and international professional literature, an evaluation and analysis of the level of tax autonomy and fiscal decentralization of the RA local self-government bodies was carried out, making comparisons with European countries.
Keywords: Regional developments